Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Metode Economic Value Added (EVA) Pada PT. Astra International Tbk – Auto 2000 Kapuk yang Terdaftar di Bursa Efek Indonesia (2018 – 2021) - Gustiyan Taufik Mahardika; Marison Sitorus; Arif Dzulfikar (Cakrawala Repositori IMWI, 2023)
The purpose of this study was to determine and analyze the continuity of financial performance at PT. Astra International Tbk which is engaged in the assembly and distribution of vehicles and spare parts. This study uses the Economic Value Added (EVA) method which is an economic added value during the period which is one way to assess the company's financial performance. The analytical method used is IC analysis, weighted cost of capital analysis (WACC), NOPAT analysis, and EVA analysis. The results of the Economic Value Added (EVA) in 2018 amounted to (Rp 117.438.000.000). Then in 2019 the value of EVA experienced a negative decrease to (Rp. 986.495.200.000). In 2019 the value of EVA experienced a negative increase to (Rp 360.005.100.000) then in 2021 it experienced a negative value decrease of (Rp 447.948,000,000.